2012
DOI: 10.1017/s1041610212000063
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life ratings for persons with dementia simultaneously reported by patients and their caregivers: the Cache County (Utah) Study

Abstract: Background Quality of Life (QOL) is frequently assessed in persons with dementia (PWD) via self- and/or proxy-report. Determinants of QOL ratings are multi-dimensional and may differ between patients and caregiver proxies. This study compares self-report and proxy QOL ratings in a population-based study of PWD and their caregivers, and examined the extent to which discrepancies in reports were associated with characteristics of the PWD. Methods The sample consisted of 246 patient/caregiver dyads from the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
58
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 27 publications
11
58
1
Order By: Relevance
“…The differences in the rating of QOL between self-report and proxy report generally depend on variables such as depressive symptoms and severity of dementia and should be recognized [55,61,62,63,64]. The QUALIDEM was developed to measure QOL in persons with dementia; however, observational instruments always have the possibility of observer bias [65].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the rating of QOL between self-report and proxy report generally depend on variables such as depressive symptoms and severity of dementia and should be recognized [55,61,62,63,64]. The QUALIDEM was developed to measure QOL in persons with dementia; however, observational instruments always have the possibility of observer bias [65].…”
Section: Discussionmentioning
confidence: 99%
“…The burden of Alzheimer’s disease (AD) is compounded by neuropsychiatric symptoms (NPS) which occur in almost all patients [1, 2], and are usually persistent [3], NPS are associated with accelerated cognitive and functional decline [4, 5], worse quality of life [6, 7], earlier institutionalization [810], and accelerated mortality [10, 11]. Depression, apathy, anxiety, agitation and irritability are the most commonly observed NPS [2, 12].…”
Section: Introductionmentioning
confidence: 99%
“…11 Moving to a care facility means to leave a known and familiar environment for an unfamiliar one, 12 and therefore the main challenge in residential care facilities is to create appropriate and supportive living environments that contribute to the QoL of older adults. 14 Previous research has shown the important role that cognitive performance 15 and loss of independence 16 has on the QoL of older adults with dementia, as well as the important negative effect of depression. theater, occupational therapy).…”
Section: Introductionmentioning
confidence: 99%